พัฒนาการนาฏกรรมจากโบราณคติ - กรุงแก้ว, วิกรม; โรจนสุขสมบูรณ์, อนุกูล (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 2 (2562): Academic Services Journal, Prince of Songkla University, 2019)
บทความนี้เป็นส่วนหนึ่งของวิทยานิพนธ์เรื่องการสร้างนาฏกรรมจากโบราณคติ โดยกล่าวถึงวัตถุประสงค์ข้อที่ 1) พัฒนาการนาฏกรรมจากโบราณคติ  เป็นวิจัยเชิงคุณภาพ ศึกษาข้อมูลจากเอกสาร สัมภาษณ์ สังเกต การสนทนากลุ่ม นำเสนอข้อมูลเชิงพรรณนา มีขอบเขตการศึกษานาฏกรรมจากโบราณคติจาก พ.ศ.2510 และพัฒนาไปสู่นาฏกรรมจากโบราณคติเรื่องพระมหาชนกจากปี พ.ศ. 2540 ถึงพระมหาชนกเดอะฟีโนมินอล ไลท์โชว์ พ.ศ. 2557 ผลการวิจัยพบว่า นาฏกรรมจากโบราณคติ คือการแสดงที่สร้างขึ้นจากคติโบราณหรือคลังสมองเชิงคุณธรรมของมนุษย์ โดยมีพัฒนาการแบ่งออกเป็น 3 ช่วงเวลา 1) เริ่มต้น เกิดขึ้นจากการเล่าเรื่องราวคติโบราณของมนุษย์ด้วยปากเปล่า (มุขปาฐะ) ในรูปแบบนิทาน ตำนานเชื่อมโยงกับปรากฏการณ์ทางธรรมชาติ 2) แพร่กระจาย การเล่าเรื่องราวประกอบการแสดงบทบาทสมมุติและเคลื่อนไหวร่างกายเพื่อดำเนินเรื่องตามอุปนิสัยของตัวละครเพื่อให้ผู้ฟังเกิดความสนใจมากขึ้น 3) พัฒนาใหม่ นำโบราณคติมาพัฒนาขึ้นเป็นนาฏกรรมโดยใช้องค์ด้านนาฏยประดิษฐ์ เช่น แสง เสียง เครื่องแต่งกาย ฉาก ท่ารำ บทร้องเข้ามามีส่วนร่วมเพื่อให้ผู้ชมได้รับอรรถรสต่อการรับชม รวมทั้งใช้เป็นเครื่องมือเพื่อสอนใจ ตลอดจนเป็นแนวทางต่อการพัฒนาคุณภาพชีวิตมนุษย์ให้ดียิ่งขึ้น โดยเฉพาะนาฏกรรมเรื่อง พระมหาชนก อันเกิดจากบทพระราชนิพนธ์ในพระบาทสมเด็จพระปรมินทรมหาภูมิพลอดุลยเดชฯ บรมนาถบพิตร ซึ่งกล่าวถึงโบราณคติด้านวิริยะบารมี (ความเพียร) และมีการพัฒนารูปแบบไปสู่นาฏกรรมพระมหาชนกในรูปแบบต่างๆ ตามยุคสมัย คำสำคัญ: พัฒนาการ, นาฏกรรม, โบราณคติ   This article is a partial study of the thesis named the development of performance from folklore which intended to explore 1) The development performance based of the folklore. Focusing on the first mentioned objective, the researcher consequently employed the qualitative researching methods consisting of literature review, interviews, observations, and focus group in order to collect the data. The scope of the study was the folklore based performances from 2510 B.E. and development the Mahajanaka Prototype in 2540 B.E. to Mahajanaka the Phenomenon Live Show. The results of the study indicate that the folklore based performance is inspired by the ancient morals or wisdoms. The development could be divided into 3 phases including 1) starting phase: the stories of the folklores were told by human through the tales or the legends by supernatural phenomenon; 2) the diffusing phase: the stories were told through the role plays and movements representing the habits of the characters; this attracted more audience; and 3) the new development phase: bringing folklore apocalypse had been developed to performance by adding choreographic elements such as light, sound, costumes, backgrounds, movements, and lyrics to the better experience watching the performances as well as using the performances as the medium for teaching and developing peoples’ quality of life. One of the outstanding examples is the performance of Mahajanaka that was inspired by the royal writing of H.M. the King Bhumibhol featuring the pertinacity. It is the prototype to the creation of various forms of performances in the following years. Keywords: development, performance, folklore